Examining Gender Relations among South Asian Immigrant Women Living with HIV in the Greater Toronto Area: Theoretical Implications - Kteily-Hawa, Roula (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
This paper focuses on South Asian immigrant women living with HIV in Toronto. Our community-based research affirmed the benefits of augmenting the social theory of gender with a focus on the local. An anti-oppressive and intersectional lens explored how multiple relations of domination and subordination affect women living with HIV. A general inductive approach identified four themes pursuant to women’s perceptions of gender relations and how they affect their risk of HIV: power, emotional attachment, gendered division of labour, and social norms. Richer understandings of how power operates between genders paves the way for theory refinement and innovative, refocused research.